WNT2-Mediated FZD2 Stabilization Regulates Esophageal Cancer Metastasis via STAT3 Signaling - Fu, Yufei; Zheng, Qi; Mao, Yingying; Jiang, Xiyi; Chen, Xin; Liu, Pei; Lv, Bin; Huang, Tuxiong; Yang, Jiao; Cheng, Yongran; Dai, Xiaoyi; Dai, Chunyan; et al. (Frontiers in Oncology, 2020)
Esophageal cancer micro environment factor WNT2 was critical in cancer metastasis. However, very little is known about WNT2 receptors and their role in the malignant progression of ESCC. The clinical significance and underlying molecular mechanisms of FZD2, one of the receptors of WNT2, was further investigated in ESCC. We found that FZD2 expression was positively correlated with WNT2 levels in clinical ESCC specimens through database analysis. Upregulated FZD2 expression was detected in 69% (69/100) of the primary ESCC cases examined, and increased FZD2 expression was significantly correlated with poor prognosis (P<0.05). Mechanistically, FZD2 induced the migration and invasion of ESCC cells by regulating the FZD2/STAT3 signalling. In vivo xenograft experiments further revealed the metastasis-promoting role of FZD2 in ESCC. Moreover, we found that the WNT2 ligand could stabilize and phosphorylate the FZD2 receptor by attenuating FZD2 ubiquitination, leading to the activation of STAT3 signalling and the initiation of ESCC cell metastasis. Collectively, our data revealed that a novel non-canonical WNT2/FZD2/STAT3 signalling axis is critical for ESCC progression. Strategies targeting this specific signalling axis might be developed to treat patients with ESCC.